Literature Study of the Sociological Approach of the Family as a Pillar of Resilience and Preparedness to Face Disasters in Indonesia - Mohammad Zainudin; Yohana Norandika Maharani; Eko Teguh Paripurno; Purbudi Wahyuni; Arif Rianto Budi Nugroho (Badan Penerbit STIEPARI Press, 2025)
Indonesia is highly vulnerable to natural disasters such as earthquakes, tsunamis, volcanic eruptions, and floods. In this context, families play a crucial role as pillars of resilience and preparedness for disasters. This study aims to review existing literature related to the role of families in building resilience and disaster preparedness in Indonesia. This study illustrates the importance of the family's role in facing various natural disasters that are common in Indonesia. The family not only functions as a basic unit in society but also as the first agent in disaster risk mitigation. Through this role, families can strengthen the capacity of individuals and communities in facing emergency situations. This literature review includes an analysis of various studies that have been conducted on family strategies in increasing resilience to disasters, including disaster education at home, provision of emergency equipment, and evacuation plans. In addition, it also discusses how government policies and community support can strengthen the role of families in disaster preparedness. The literature review shows that families with good knowledge and preparedness can reduce the negative impact of disasters. Families that have implemented disaster preparedness practices tend to be more able to survive and recover quickly after a disaster occurs. Government and community support are also found to be very important in strengthening family resilience. The purpose of this study is to provide a comprehensive overview of the important role of families in facing disasters in Indonesia and to identify factors that support family resilience. This study emphasizes that families have a vital role in disaster preparedness and resilience. With appropriate education, government support, and community involvement, families can be a key pillar in disaster mitigation strategies, which in turn will reduce losses and accelerate the post-disaster recovery process